An analytical study on fleet utilization at Pelangi Air Sdn. Bhd. / Shamshinar Mohd. Rusli - Mohd. Rusli, Shamshinar (1995)
It is a recognized fact that maximum fleet utilization is one of the key to an operational success of an airline. Being a small airline, Pelangi Air measured the fleet utilization through the operating cost for each sector, the number of passenger carried and load factor. This research attempts to analyze Pelangi Air's fleet utilization by evaluating the airline's passenger load, load factor and the operating cost for four selected routes. It is hope that the finding of the analysis can help determine Pelangi Air growth in the coming years.